Alloknesis and hyperknesis—mechanisms, assessment methodology, and clinical implications of itch sensitization. Issue 7 (July 2018) - Andersen, Hjalte Holm; Akiyama, Tasuku; Nattkemper, Leigh Ann; van Laarhoven, Antoinette; Elberling, Jesper; Yosipovitch, Gil; Arendt-Nielsen, Lars
Abstract : Abstract: Itch and pain share numerous mechanistic similarities. Patients with chronic itch conditions (for instance atopic dermatitis or neuropathic itch) often experience symptoms such as mechanical alloknesis and hyperknesis. These dysesthesias are analogous to the pain-associated phenomena allodynia and hyperalgesia, which are often observed, for example, in neuropathic pain conditions. Mechanical itch dysesthesias represent abnormal sensory states (caused by neuroplastic changes), wherein considerable itch is evoked, for instance by light cutaneous stimuli such as from clothing (alloknesis), or where increased itch is perceived in response to normally itch-evoking stimuli (hyperknesis). These itch sensitization phenomena have been explored in experimental human studies, observed in chronic itch patients, and in animal models of itch. Limited attention has been paid to these sensory phenomena in clinical studies, and it is unknown how they respond to antipruritics. Psychophysical quantitative sensory testing can quantify the presence, severity, and spatial extent of itch dysesthesias in chronic itch patients, providing a proxy measurement of itch sensitization. This review outlines current assessment techniques, knowledge on the mechanisms of mechanical alloknesis and hyperknesis, and presents the diverse results derived from clinical studies exploring the presence of itch dysesthesias in chronic itch patients. A key role of quantitative sensory testing and neuronal sensitization in patients with chronic pain is accepted and used in clinical assessments. However, the precise mechanisms and potential clinical implications of itch sensitization in chronic itch patients remain to be evaluated.